Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.5935/0004-2749.20160050
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on optical performance and visual outcomes between two diffractive multifocal lenses: AMO Tecnis® ZMB00 and AcrySof® IQ ReSTOR® Multifocal IOL SN6AD1

Abstract: Purpose: To compare the optical performance and visual outcomes between two diffractive multifocal lenses: AMO Tecnis® ZMB00 and AcrySof® ReSTOR® SN6AD1. Methods: This prospective, non-randomized comparative study included the assessment of 74 eyes in 37 patients referred for cataract surgery and candidates for multifocal intraocular lens implants. Exclusion criteria included existence of any other eye disease, previous eye surgery, high axial myopia, preoperative corneal astigmatism of >1.00 cylindrical diopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Previous in vitro tests indicated that the tilt of an MfIOL has a significant effect on visual quality [14], and our follow-up correlation analysis confirmed that MfIOL tilt correlated positively with the aberration value. However, in previous studies, there was no significant difference in HOAs between these two groups after a short follow-up period [4,28]. A possible explanation involves the contraction of the capsular bag, which occurs more frequently with lenses made of soft materials.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Previous in vitro tests indicated that the tilt of an MfIOL has a significant effect on visual quality [14], and our follow-up correlation analysis confirmed that MfIOL tilt correlated positively with the aberration value. However, in previous studies, there was no significant difference in HOAs between these two groups after a short follow-up period [4,28]. A possible explanation involves the contraction of the capsular bag, which occurs more frequently with lenses made of soft materials.…”
Section: Discussionmentioning
confidence: 77%
“…MfIOLs are designed to improve the near vision of patients after cataract surgery and potentially allow the patient to read and write. Previous studies have shown that the implantation of SN6AD1 and ZMB00 MfIOLs can improve both distance and near vision [4,10,11].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The AcrySof IQ ReSTOR +2.5 D multifocal lens has been designed to allow better uncorrected intermediate vision and reduce glare and halos compared with previous, higher-add models. 11,[14][15][16][17][18][19][20] This lens was designed for patients who want to participate in activities requiring more intermediate (53 cm/21 in) and distance (4 m/13 ft) vision, 21 and the lens is intended to result in a lower incidence of glare because the central optic is designed for distance. A similar lens, the AcrySof IQ ReSTOR +3.0 D was designed for patients who desire a broad range of vision from 16 inches (40 cm) to distance.…”
Section: Introductionmentioning
confidence: 99%